The Regional Impact of Nanjing Urban Rail Network Accessibility on Residential Property Purchase Intention - Caiyun Song; Jacky Mong Kwan Watt (Digital Innovation : International Journal of Management, 2025)
This study examines the regional impact of Nanjing's urban rail network accessibility on residential property purchase intention, highlighting the interplay between transportation infrastructure and real estate dynamics. As urban rail networks enhance connectivity, they are expected to influence buyer behavior and property values. The research explores how factors such as environmental quality, market conditions, and psychological influences shape purchase intentions among potential buyers. By analyzing data from various neighborhoods affected by the urban rail system, the findings reveal a significant positive correlation between accessibility and property purchase intention, with buyers increasingly valuing sustainable living environments. This study contributes to the understanding of the role of transportation infrastructure in urban development and its impact on residential real estate markets, drawing on insights gathered from a sample of 390 participants in the Nanjing area.